The Influence of Work Culture Motivation, Job Satisfaction on Employee Performance with the Remuneration System as a Moderator Variable of Ibn Khaldun University Bogor - Septianti, Ajeng; Indupurnahayu, Indupurnahayu; Ramly, Amir Tengku; Sofianti, Evin (PT FORMOSA CENDEKIA GLOBAL, 2024)
The problems are about employee performance analysis based on motivation, work culture, satisfaction, moderated by the remuneration system. The purpose of the study was to find out the remuneration system affects motivation, culture, and job satisfaction on employee performance at Ibn Khaldun University Bogor. This study uses a quantitative descriptive method. Data collection used a questionnaire with a sample of 90 educator employees at Ibnu Khaldun University Bogor. This analysis uses multiple linear regression. The results of the study were that work motivation had a significant effect on employee performance, work culture had a significant effect on employee performance, job satisfaction did not have a significant effect on employee performance, and work motivation had a significant effect on employee performance after interacting with remuneration variables. Work culture has a significant effect on employee performance after interacting with remuneration variables. Job satisfaction has a significant effect on employee performance after interacting with remuneration variables. The results of this study show that motivation, work culture affect performance, while motivation does not affect employee performance.